Prediction Research of Annual Death Numbers and Annual Coal Production in China's Coal Industry Based on Simple Linear Regressio - WANG Wen-cai; QIAO Wang; WANG Rui-zhi; LI Gang (Gong-kuang zidonghua, 2010)
In order to predict development status of future safety situation of China's coal industry, a prediction model of simple linear regression for annual death numbers and annual coal production in China's coal industry was established, and the model was used to predict annual death numbers and annual coal production of China's coal industry in three years. The prediction result showed that the model has certain feasibility, which can provide reliable theoretical basis for predicting safety situation of China's coal industry.